Digital infrastructure quality and stock market development: Evidence from panel data with the conditional role of FDI - Saif, Saeed; Sudarsono, Heri; Saif, Hashem A. A.; Ben Rhouma , Arij (Jurusan Ilmu Ekonomi, Fakultas Bisnis dan Ekonomika, Universitas Islam Indonesia, 2026)
Purpose – This study examines the impact of digital infrastructure quality on stock market capitalization and evaluates the moderating role of foreign direct investment (FDI).Methods – Using panel data from 10 countries over the period 2012–2023, the study employs random effects estimation with robust standard errors to ensure consistency under heteroskedasticity.Findings – The results show that fixed broadband significantly enhances stock market capitalization, while internet usage is statistically insignificant. High-technology exports exhibit a negative association with market capitalization, whereas FDI contributes positively and its interaction with digitalization indicates a declining marginal effect of internet usage at higher levels of FDI.Implication – This finding emphasizes that digital quality is more important than access alone in promoting financial market development.Originality – This study advances the literature by focusing on digital infrastructure quality rather than digital adoption and by providing new cross-country evidence on the joint roles of digitalization, FDI, and high-technology exports in stock market development AbstrakTujuan – Penelitian ini menganalisis pengaruh kualitas infrastruktur digital terhadap kapitalisasi pasar saham serta peran moderasi investasi asing langsung (FDI).Metode – Penelitian menggunakan data panel dari 10 negara pada periode 2012–2023 dengan pendekatan random effects dan robust standard errors untuk meningkatkan ketahanan estimasi.Temuan – Hasil penelitian menunjukkan bahwa fixed broadband berpengaruh positif dan signifikan terhadap kapitalisasi pasar saham, sementara penggunaan internet tidak signifikan. Ekspor teknologi tinggi berhubungan negatif dengan kapitalisasi pasar, sedangkan FDI berkontribusi positif dan efek marginal penggunaan internet cenderung menurun pada tingkat FDI yang lebih tinggi.Implikasi – Temuan ini menekankan bahwa kualitas digital lebih penting dibandingkan akses semata dalam mendorong perkembangan pasar keuangan.Orisinalitas – Studi ini memperkaya literatur dengan berfokus pada kualitas infrastruktur digital, bukan sekadar adopsi digital, serta memberikan bukti lintas negara mengenai peran digitalisasi, FDI, dan ekspor teknologi tinggi dalam mendorong perkembangan pasar saham.